Study on improving the gas extraction efficiency by deep-hole pre-split blasting in Wulunshan Coal Mine, Guizhou - Yang, Junwei; Zheng, Xigui; Liu, Chengwei; Zhai, Wenjie; Liu, Hongyang; Zhang, Peng (Frontiers in Earth Science, 2022)
Due to the low permeability of the coal seam and low gas extraction rate in conventional boreholes in Wulunshan Coal Mine in Guizhou. In this paper, deep hole pre-split blasting method is applied to study the improvement of gas extraction efficiency by increasing the permeability of coal seam. The study comprehensively expounds the process in which deep hole pre-split blasting method is applied in improving the gas extraction efficiency, and proposes a numerical simulation method that combines ANSYS/LS-DYNA and COMSOL Multiphysics. Using the method, the initiation of blasting fracture channels and the subsequent influence on the gas extraction range have been comprehensively and directly researched and analyzed. Finally, a theoretical research has been verified by field experiments. According to the recorded simulation of the Wulunshan Coal Mine, the exposed area of the blasting borehole was 42 times the size of the conventional drilling borehole, and the pressure relief space was 1050 times that of the conventional, which can connect about 32m3 of coal. Compared with conventional drilling boreholes, in the process of gas extraction, the control range of the controlled pressure reduction was 4~7 times, the range of gas pressure reaching the standard was 25 times, and the peak pressure was reduced by 3~5 times. The average gas concentration was 1.85 times that of conventional boreholes, and the cumulative gas extraction volume of blasting boreholes was 4.48 times that of conventional boreholes. The research results prove that the application of blasting and permeability enhancement in the coal seam with high gas content and low permeability can effectively improve the gas extraction efficiency in the Wulunshan Coal Mine in Guizhou.